Hubungan Self Control dengan Kecenderungan Adiksi Media Sosial Tiktok di SMAN X Tambun Selatan: Hubungan Self Control dengan Kecenderungan Adiksi Media Sosial Tiktok di SMAN X Tambun Selatan - Rhozyania Safitri; Netty Merdiaty (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
This study explains the relationship between self-control and the tendency of social media addiction to Tiktok in students of SMAN X Tambun Selatan. This study aims to determine whether there is a relationship between Self control and the tendency of social media addiction in students of SMAN X Tambun Selatan, with a total of 139 subjects using quantitative research methods. Subjects were determined using purposive sampling techniques based on predetermined characteristics and subject willingness. This study uses the Self control scale instrument from Averill and the Social Media Addiction Tendency scale from Griffiths. The correlation test in this study used the non-parametric correlational analysis method from Spearman with a correlation coefficient of 0.771 with a significance level of 0.000 which indicates that p> 0.05 which means there is a relationship between Self control and Social Media Addiction Tendencies. As for suggestions that can be given by researchers, namely entering into groups or outside communities so that addiction to social media does not occur.